The Role of Political Party Elites in Reconciling Identity Political Conflicts After the 2019 Presidential Election: A Consensus Perspective - Ulum, Bahrul (TEMALI : Jurnal Pembangunan Sosial, 2024)
The research aims to analyze the role of political party elites in reconciling identity political conflicts after the 2019 presidential election carried out by political party elites from the perspective of Ralf Dahrendorf's social conflict theory. The research approach used is qualitative with descriptive methods. The data was collected using documentation, namely journal articles and news articles about reconciliation after the 2019 presidential election—news articles taken from kompas and detik.com. The analysis used is content analysis. The findings from this research are that the consensus agreed upon by the political party elites that intersect has a significant influence on society, which previously experienced polarization due to the strengthening use of identity politics in the 2019 presidential election. This research is useful in the realm of political sociology and also social development. Based on the research findings, this research is novel in the perspective that conflicts that occur between groups can be negotiated and made mutual agreements for the progress of a larger organization.